Poisoning with e-cigarette liquid (VPG Power Smoke Baze) - case report - Marlena Zając; Dariusz Gruca; Marcin Wais (Journal of Education, Health and Sport, 2023)
Introduction and purpose: E-cigarettes have emerged as an alternative to traditional tobacco smoking. Toxicological studies have investigated the composition and potential toxicity of e-cigarette liquid components. While they are generally considered less harmful than combustible cigarettes, cases of poisoning associated with e-cigarette liquid ingestion or exposure have been reported.